Effects of coenzyme Q10 supplementation on the anthropometric variables, lipid profiles and liver enzymes in patients with non-alcoholic fatty liver disease (Bangladesh Journal of Pharmacology, 2015)
This randomized double-blind placebo-controlled trial was conducted on 41 patients with non-alcoholic fatty liver disease. Patients in intervention group received 100 mg/day coenzyme Q10 (CoQ10) for four weeks. There was a significant reduction in waist circumference and aspartate aminotransferase concentrations after CoQ10 supplementation (p